2001
DOI: 10.1088/0031-9155/46/2/308
|View full text |Cite
|
Sign up to set email alerts
|

Experimental examination of a targeted hyperthermia system using inductively heated ferromagnetic microspheres in rabbit kidney

Abstract: It is known that significant heating can be generated by magnetic hysteresis effects in small ferromagnetic particles exposed to a rapidly alternating magnetic field. If such particles can be made to infiltrate the vascular bed surrounding a tumour by intravascular infusion then it may be possible to generate sufficient heating to destroy the tumour by hyperthermia. One of the constraints on such a technique is the limited amount of magnetic material that can be delivered to a tumour via the intravascular rout… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…Jordan et al [113] have shown that SAR can be optimized through magnetic fractionation of the starting colloid, i.e., by selecting a small particle size window from the original size distribution. In addition to particle size and shape influence on heating power [114][115][116], the magnetic field amplitude and frequency must be considered when comparing experiments in Table IV.…”
Section: Hyperthermiamentioning
confidence: 99%
“…Jordan et al [113] have shown that SAR can be optimized through magnetic fractionation of the starting colloid, i.e., by selecting a small particle size window from the original size distribution. In addition to particle size and shape influence on heating power [114][115][116], the magnetic field amplitude and frequency must be considered when comparing experiments in Table IV.…”
Section: Hyperthermiamentioning
confidence: 99%
“…[47] Wu et al and Jones and Winter used MNPs in the treatment of hepatocellular carcinoma embolization. [47,48] In the follow up of these initial experiments, some research teams used animals to show the effectiveness of this method. [48] • Lubbe and co-workers conducted the Stage-I clinical study using magnetically focused medication transport.…”
Section: The Evolution Of Magnetic Drug Deliverymentioning
confidence: 99%
“…[47,48] In the follow up of these initial experiments, some research teams used animals to show the effectiveness of this method. [48] • Lubbe and co-workers conducted the Stage-I clinical study using magnetically focused medication transport. [49] Electrostatic connections involving phosphate units were attached to the granular exterior and amino groups contained inside the medication.…”
Section: The Evolution Of Magnetic Drug Deliverymentioning
confidence: 99%
“…The applications of iron particles, with various sizes, compositions, and shapes, in the biomedical fields have attracted worldwide attention during the past few years . Nonfunctionalized iron particles only have limited applications.…”
Section: Introductionmentioning
confidence: 99%
“…The surface functionalized iron particles with thin organic layers are commercially available, such as Feridex (dextran associated iron oxide) for contrast enhanced MRI, and are carboxylic acid functionalized for bio‐molecule separations . For hyperthermia applications, the heat generated from the iron particles by magnetic hysteresis effects result from on‐off switching of the magnetic field . Hence, high magnetic saturation properties of the iron particles must be maintained if the particles are subjected to surface coating.…”
Section: Introductionmentioning
confidence: 99%